Management of the Blueberry Gall Midge on Southern Highbush Blueberries in Florida - Marice Lopez; Patricio Munoz; Oscar Liburd (EDIS)
The blueberry gall midge (BGM) is one of the most important pests of southern highbush blueberries in Florida. Monitoring for BGM using clear sticky traps or bucket traps should begin as early as November. Chemical control should be applied right before bud break and then ten days after bud break, or when at least two BGM are found on traps. Other management practices include the use of younger mulch, using potentially resistant cultivars, and chemical control such as Movento with Induce and Apta in rotation to avoid resistance development. Applications should also be timed with larval and adult emergence for optimal insecticide efficacy.